Using Credit Cards to Streamline the Use of Resources - Farideh Moradi; Mohammad Mohseni; Majid Nakhaee; Ali Soroush (Baqiyatallah University of Medical Sciences, 2018)
Health organizations are one of the most important organizations of every country. The responsibility and duty of such organizations are to supply, maintain, and improve the individuals of society. The hospital as a health organization has long been one of the most important medical service providers.1 Increasing health system costs all over the world have become a main concern of health system managers and decision makers.2 The health system of Iran, like others, faces the challenge of major increases in costs. While the total index of expenses in Iran has become 30 times greater in the past 20 years, expenses in the health sector have increased to a figure 71 times higher.